Implications of Science Learning Models for Enhancing Students’ Science Process Skills in Elementary Schools in the Digital Era - Hairunnisa; Naimah; Sigit Prasetyo; Sholeh (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the implications of science learning models for strengthening elementary students’ Science Process Skills (SPS) in the digital era. The research addresses the problem of uneven development of SPS indicators, particularly higher-order and language-intensive skills, in primary science classrooms. The study aims to describe the implementation of science learning models, the profile of students’ SPS, the integration of digital technology, and assessment practices in Grade V science learning. A qualitative case study was conducted in two public elementary schools in Tanjung pinang Timur using purposive sampling. Data were collected through classroom observations, semi-structured interviews with two teachers and four students, and documentation, and were analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings reveal that science instruction is dominated by group discussions and hands-on experiments, with the emerging use of project-based learning. Students demonstrate strong foundational SPS (observing, classifying, measuring) but show weaknesses in predicting, hypothesizing, concluding, and communicating due to confidence and language barriers. Digital media support conceptual understanding and engagement but are limited by device availability and preparation time. Assessment practices remain largely product-oriented and group-based. The study concludes that strengthening SPS requires pedagogy-led technology integration, targeted scaffolding for scientific reasoning and communication, and indicator-based assessment aligned with the Kurikulum Merdeka.